How can pharmacists contribute to anaemia management? A review of literature and exploratory study on pharmacists' role in anaemia - Sherly Meilianti; Christopher John; Catherine Duggan; Leonila O'campo; Ian Bates (Elsevier, 2023)
Background: Iron deficiency anaemia (IDA) is the leading cause of anaemia globally, most frequently found in children and pregnant women. With their increasing role in the healthcare system, pharmacists may contribute to the management of anaemia. Through the International Pharmaceutical Federation (FIP) Multinational Needs Assessment Programme, the FIP explored the contribution of pharmacists in anaemia, specifically IDA, focusing on five countries: India, Indonesia, Malaysia, Philippines and Singapore. Objective: To explore information on pharmacists' roles in a variety of settings related to 1) IDA management; 2) education and training needed to support the roles; and 3) barriers and enablers to expanding or developing the roles. Methods: This study involved a literature review and a focus group discussion with twelve participants selected purposively and nominated by national professional leadership bodies across five countries. A literature search was conducted using PubMed Database. A focus group discussion explored pharmacists' roles, education and training needs, as well as barriers and enablers to support their roles in anaemia management, specifically in IDA. A codebook thematic analysis approach was conducted according to the study objectives. Results: Sixteen articles were included in the analysis. The pharmacists' roles in anaemia identified from literature ranged from patient management and monitoring, collaboration with other healthcare professionals and involvement in guideline development, in which the roles vary according to the workplace. Twelve participants attended the focus group discussion. Participants highlighted pharmacists' roles in screening and detection, medication therapeutic management, patient counselling and patient monitoring. Participants emphasised a need for guidelines or toolkits with subsequent training or workshops to support their competency development in anaemia. Monitoring the success of pharmacist delivered anaemia programmes was recommended to support advocating for active pharmacist roles. Conclusion: Pharmacists have a growing opportunity to contribute to achieving the global targets on anaemia through their involvement in screening and managing anaemia and increasing anaemia awareness among the patients and community.